2017
DOI: 10.1007/s00422-017-0732-z
|View full text |Cite
|
Sign up to set email alerts
|

A neural network model for familiarity and context learning during honeybee foraging flights

Abstract: How complex is the memory structure that honeybees use to navigate? Recently, an insect-inspired parsimonious spiking neural network model was proposed that enabled simulated ground-moving agents to follow learned routes. We adapted this model to flying insects and evaluate the route following performance in three different worlds with gradually decreasing object density. In addition, we propose an extension to the model to enable the model to associate sensory input with a behavioral context, such as foraging… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
27
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
4
2

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(30 citation statements)
references
References 68 publications
2
27
0
Order By: Relevance
“…The hypothesis appears congruent with 61 numerous behavioral observations [29][30][31][32][33][34][35][36]. Furthermore, there are now robots and 62 simulated agents that navigate autonomously via familiarity [1,18,[37][38][39], and some 63 studies [40, 41] have suggested how neural tissue, such as the central complex and 64 mushroom bodies [42-51], might be organized to accommodate familiarity-based 65 navigation. 66 June 10, 2020 5/34Navigation by familiarity with a local sensor 67In this paper, we consider the hypothesis that the dense fields of peg sensilla on pectines 68 are analogous to the tightly packed ommatidia in compound eyes, detecting matrices of 69 chemical and textural information that are used for navigation by familiarity.…”
supporting
confidence: 57%
“…The hypothesis appears congruent with 61 numerous behavioral observations [29][30][31][32][33][34][35][36]. Furthermore, there are now robots and 62 simulated agents that navigate autonomously via familiarity [1,18,[37][38][39], and some 63 studies [40, 41] have suggested how neural tissue, such as the central complex and 64 mushroom bodies [42-51], might be organized to accommodate familiarity-based 65 navigation. 66 June 10, 2020 5/34Navigation by familiarity with a local sensor 67In this paper, we consider the hypothesis that the dense fields of peg sensilla on pectines 68 are analogous to the tightly packed ommatidia in compound eyes, detecting matrices of 69 chemical and textural information that are used for navigation by familiarity.…”
supporting
confidence: 57%
“…There is no evidence that complex learning in insects involves sentience ( Giurfa, 2013 ; Chittka, 2017 ). There is no need to assume conscious awareness in either insects or molluscs in order to explain complex behaviors when non-conscious neural networks can effectively account for such abilities ( Ardin et al, 2016 ; Faghihi et al, 2017 ; Goldschmidt et al, 2017 ; Müller et al, 2017 ; Peng and Chittka, 2017 ; Perry et al, 2017 ; Roper et al, 2017 ).…”
Section: Behavior Is Not Sufficient To Infer Conscious Awarenessmentioning
confidence: 99%
“…In Drosophila, sparse coding was found to reduce overlap between odor representations and facilitate their discrimination (Lin et al, 2014). Consequently, sparse coding is an essential feature of plasticity models for olfactory learning in insects (Huerta and Nowotny, 2009;Wessnitzer et al, 2012;Ardin et al, 2016;Peng and Chittka, 2016;Müller et al, 2018), and theoretical work has emphasized the analogy of the transformation from a dense code in projection neurons (PNs) to a sparse code in Kenyon cells (KCs) with dimensionality expansion in machine learning methods (Huerta and Nowotny, 2009;Mosqueiro and Huerta, 2014;Schmuker et al, 2014).…”
Section: Introductionmentioning
confidence: 99%